Simulation of Dynamic System Model in the Development of Green Environmental Tourism to Increase Economic Growth in Pangandaran - Dedeh Maryani (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2017)
Pangandaran as a new autonomous region has a great potential in tourism, Pantai Pangandaran, Cagar Alam Pananjung, Pantai Batu Hiu, Pantai Batu Karas, Pantai Madasari, Green Canyon, Citumang. Therefore, this vision is: